2019
DOI: 10.1021/acs.jpcc.8b11268
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Hg0 and HgCl2 Adsorption Properties in UiO-66 from Flue Gas Using Molecular Simulations

Abstract: Adsorption of mercury species in porous materials is an attractive means to capture these species from flue gas, but the lack of reliable force fields (FFs) for Hg 0 and HgCl 2 has made modeling adsorption of these important species challenging. We introduce a robust set of FFs to describe interactions between Hg 0 , HgCl 2 , and other flue gas components and UiO-66, a prototypical metal−organic framework. Using these FFs, adsorption isotherms in UiO-66 for pure components and mixtures of Hg 0 , HgCl 2 , N 2 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Compelling evidence exists that molecular modeling can accurately predict the adsorption isotherms of CO 2 and similar species in a wide range of MOFs. ,, The large pore volumes and surface areas of MOFs, coupled with a suggested process design made them appealing materials as adsorbents. , Here we extend our focus to a bulk mixture of CO 2 /N 2 at compositions relevant to postcombustion flue gas. Real flue gas contains other contaminants including H 2 O, O 2 , CO, SO x , NO x , and Hg species. The presence of these contaminants could impact adsorption properties of primary components and the stability of adsorbents. Air Liquide has demonstrated that dry flue gas feeds can be achieved by appropriate system design combined with a subambient heat exchanger . We therefore focus on adsorptive separation of CO 2 from a dry bulk binary mixture of CO 2 /N 2 with molar composition 0.14/0.86 with no other components.…”
Section: Methodsmentioning
confidence: 99%
“…Compelling evidence exists that molecular modeling can accurately predict the adsorption isotherms of CO 2 and similar species in a wide range of MOFs. ,, The large pore volumes and surface areas of MOFs, coupled with a suggested process design made them appealing materials as adsorbents. , Here we extend our focus to a bulk mixture of CO 2 /N 2 at compositions relevant to postcombustion flue gas. Real flue gas contains other contaminants including H 2 O, O 2 , CO, SO x , NO x , and Hg species. The presence of these contaminants could impact adsorption properties of primary components and the stability of adsorbents. Air Liquide has demonstrated that dry flue gas feeds can be achieved by appropriate system design combined with a subambient heat exchanger . We therefore focus on adsorptive separation of CO 2 from a dry bulk binary mixture of CO 2 /N 2 with molar composition 0.14/0.86 with no other components.…”
Section: Methodsmentioning
confidence: 99%
“…HgCl 2 has been shown to adsorb far more strongly in porous adsorbents in comparison to CO 2 or N 2 , leading to examples in which extremely low levels of HgCl 2 can dramatically change the adsorption capacity of adsorbents for CO 2 . 11 In each of these examples, information from “realistic” streams reveals issues that might become critical “showstoppers” 12 on the path to real-world implementation that cannot be deduced from the typical single-component or idealized mixture experiments that are common in the research literature.…”
Section: Hierarchy Of Separations Complexitymentioning
confidence: 99%
“…Multiple examples are known of adsorbents that are stable in pure water and also on exposure to dry acid gases such as SO 2 but degrade rapidly in a humid stream containing ppm levels of SO 2 . This occurs because of synergistic effects between water and SO 2 . HgCl 2 has been shown to adsorb far more strongly in porous adsorbents in comparison to CO 2 or N 2 , leading to examples in which extremely low levels of HgCl 2 can dramatically change the adsorption capacity of adsorbents for CO 2 . In each of these examples, information from “realistic” streams reveals issues that might become critical “showstoppers” on the path to real-world implementation that cannot be deduced from the typical single-component or idealized mixture experiments that are common in the research literature.…”
Section: Hierarchy Of Separations Complexitymentioning
confidence: 99%
“…They found that the adsorption energy for CO 2 in the pore of the UiO‐66 was about (−30.32 KJ/mol), which is in good consistent with the experimental Q ST results. In 2019 Tang et al [123] . used the MD and the force field method in predicting the adsorption properties of Hg compounds and CO 2 on the UiO‐66.…”
Section: Co2 Capture By Uio‐66mentioning
confidence: 99%